Study of Soil Under Intercropping of Legumes in Hybrid Maize - Roy, S.B.; Shahani, M.N. (Journal of Soil and Water Conservation, 2022)
Legumes have been accorded a prominent place in the crop rotation and crop mixture from times immemorial and their soil enriching qualities were recognised when the science of Chemistry and Biology were in their infancy. Continuous grain farming without adding any thing to field has depleted the Indian soils to such an extent that most of the soils have become unproductive and uneconomical for crop production. These soils are only left with approximately 0.03 to 0.07 and 0,6 per cent nitrogen and organic carbon respectively whereas soils of Europe and America contain 0.10 per cent nitrogen and 3.00 per cent organic carbon. It is, therefore, imperative that efforts must be concentrated on nitrogen and organic carbon economy of our soil and from this stand point, greater attention slyvyld be focused to mixed cropping and intercropping of legumes with cereals. Legume intercropping in wider row spacing of hybrid maize may improve the nutrient status of the soil.